Coping, Cognitive Emotion Regulation, and Burnout in Long-Term Care Nursing Staff: A Preliminary Study. (January 2019) - Bamonti, Patricia; Conti, Elizabeth; Cavanagh, Casey; Gerolimatos, Lindsay; Gregg, Jeffrey; Goulet, Carol; Pifer, Marisa; Edelstein, Barry
Direct care workers (e.g., certified nursing assistants [CNAs]) employed in long-term care (LTC) are particularly vulnerable to the experience of burnout, yet they have received relatively less research attention compared to Licensed Practical Nurses and Registered Nurses. Within the burnout literature, evidence suggests that the deployment of certain coping strategies influences levels of burnout. The current study examined the extent to which coping (e.g., problem-focused, emotion-focused, and dysfunctional coping) and cognitive emotion regulation strategies (e.g., positive reappraisal) predicted burnout after controlling for covariates (age, sleep duration). Fifty-six CNAs were surveyed at four skilled nursing facilities in the United States. Dysfunctional coping was significantly associated with emotional exhaustion and depersonalization. Among cognitive emotion regulation strategies, positive reappraisal was significantly associated with depersonalization. Shorter sleep duration was associated with significantly greater depersonalization. Findings suggest the need to develop interventions for CNAs aimed at reducing dysfunctional coping strategies and increasing sleep duration.